Ovum Pick-up in Ruminants - Nanda, Rishi; Kumar, Anjali; S, Senthamilan; Doneriya, Gurudutt; Punetha, Meeti; Singh, G.; Chouhan, VS (Animal Reproduction Update, 2022)
Ovum Pick-up (OPU) associated with IVF has become advancement in ruminant reproduction. Transvaginal OPU guided by ultrasound is a non- invasive technique for cumulating oocytes from Graafian and antral follicles from live donor animals especially from cattle. Laparoscopic OPU in combination with in vitro embryo production increases the possibility of obtaining viable offspring in small ruminants. OPU does not impede with the usual reproduction and production performance of the donor animals and can be apply in various physiological states and circumstances of animals like different ages and reproductive disorders. The persistent collection of oocytes through OPU techniques concedes us to acquire the highest possible progeny of animals with merit genetic value, genetic improvement and advancement in animal selection. Here, we are presenting an overview of OPU from ruminants with factors affecting their outcome.
Keywords: buffalo; cattle; Embryo; Follicle; Oocytes; Superovulation